Is Chronic Inflammation a Possible Cause of Obesity-Related Depression? - Olszanecka-Glinianowicz, Magdalena (Hindawi Publishing Corporation, 2009)
Adult obesity has been associated with depression, especially in women. Whether depression leads to obesity or obesity causes depression is unclear. Chronic inflammation is observed in obesity and depression. In 63 obese women without additional diseases depression level was assessed with the Beck's questionnaire. After evaluation of depression level study group was divided into groups according to the mood status (A—without depression, B—mild depression, and C—severe depression), and serum concentration of TNF-α, sTNFs, leptin, and IL-6 were measured by ELISA. No differences in age, body mass, BMI, and body composition were observed in study groups. We did not observe differences of serum concentrations of TNF-α, sTNFRs, leptin, and IL-6 between subgroup A and subgroups B and C. It seems that circulating adipokines did not exert influence on depression levels in obese women.